Universities of China: Current Status and Global Development Strategy Until 2035 - Tatiana L. Guruleva (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2020)
Introduction. Now China is completing the “State program for medium and long-term reform and development of education for 2010–2020.” The results achieved during the implementation of this program and the new strategy for the development of China’s education, including in the field of higher education and higher education institutions, are becoming a new subject of research in domestic science and require careful study. The purpose of the study is to characterize the current state of Chinese universities and identify a strategy for their development until 2035.